PENGARUH KINERJA KEUANGAN DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Food and Beverage Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Aminatur Rifqiah; Abdul Wahid Mahsuni; Hariri Hariri (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this study are: 1) to determine the effect of financial performance through the ROA and ROE proxy on firm value. 2) to determine the effect of GCG through managerial ownership and audit committee proxies on firm value. In food and beverage companies on the Indonesia stock exchange.The population in my research is food and beverage companies listed on the Indonesia stock exchange in 2016-2018. The method used to analyze is multiple linear regression. The results of this study provide testimony of financial performance with the return on asset proxy has no significant effect on firm value while the return on equity proxy has a significant effect on firm value and for good corporate government with managerial ownership proxies and audit committees have no significant effect on firm value.Keywords: corporate value, financial performance, good corporate government